The Risk of Facebook Social Media Network on Social Security (Raparin Journal of Humanities (RJH), 2020)
Social security, which is considered as a part of national or state security, has great role in developing and advancing society. In this day and age, as we live in a world of development and technology, social security is under various types of threats and risks in most societies. The Press, through its different channels and means, plays a great role in creating and fostering this risk to destabilize social security. This, then, has necessitated many countries to restrict and curb some media outlets and journalists within legal boundaries. Accordingly, the emergence of the social media outlets in general, and Facebook, as a new social media network in particular, has increased the afore-mentioned risks and threats on social security.The aim of this paper is an attempt to find the range of the risk that comes out of Facebook on social security in Kurdistan region in general, and Erbil in particular.